PELIBATAN ORANG TUA DALAM PROSES PENDIDIKAN GUNA MENINGKATKAN PRESTASI BELAJAR SISWA - Moh Rifa’i; Sulton Sulton (Jurnal Manajemen Pendidikan, 2026)
The background of this research is rooted in the prevalence of the sociocultural phenomenon of "pasrah bongkokan" (total surrender of educational responsibility) and parental burnout in the modern era, which triggers a disintegration of communication between Islamic boarding schools (pesantren) and parents, thereby threatening the quality of students' achievements. This study aims to deeply analyze the management strategies of parental involvement in improving students' academic performance and Al-Qur'an memorization (Tahfidz) targets at SMP Darul Musthofa, Pakuniran, Probolinggo. The research method employed is a qualitative approach with a descriptive case study design. Data collection was conducted through in-depth interviews, observation, and documentation studies, while data analysis applied the interactive model of Miles, Huberman, and Saldana. The results indicate that SMP Darul Musthofa successfully orchestrated partnership mechanisms through a combination of periodic formal face-to-face meetings and the optimization of daily digital WhatsApp coordination groups. The integration of theological values (eschatological responsibility) and family social capital proved effective in reducing parents' cultural resistance, eroding passive attitudes, and triggering an acceleration of student achievements in both tahfidz (15 juz in 6 months) and regional-level science olympiads. The implication of this study emphasizes that the success of a contemporary pesantren curriculum cannot rely solely on the institution, but demands a managerial reconstruction that converts religiosity into a driving force for active parental participation in a holistic learning ecosystem.